2020
DOI: 10.1039/c9en00448c
|View full text |Cite
|
Sign up to set email alerts
|

Harmonizing across environmental nanomaterial testing media for increased comparability of nanomaterial datasets

Abstract: The chemical composition and properties of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 128 publications
(144 reference statements)
0
19
0
Order By: Relevance
“…In general, nanomaterial surfaces have high free energy; therefore, thermodynamic driving forces act to minimize the surface energy, and consequently, nanomaterials will suffer physical and chemical transformations, such as dissolution, agglomeration, and surface chemistry modifications, upon interaction with biological and environmental media. All these transformations are dependent on medium composition and exposure conditions, including solution pH, ionic strength and composition [ 22 , 50 ]. The synthetized GO shows a high dispersion stability in ultrapure water up to 72 h, monitored by UV–VIS and DLS measurements ( Figure S2, supplementary information ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, nanomaterial surfaces have high free energy; therefore, thermodynamic driving forces act to minimize the surface energy, and consequently, nanomaterials will suffer physical and chemical transformations, such as dissolution, agglomeration, and surface chemistry modifications, upon interaction with biological and environmental media. All these transformations are dependent on medium composition and exposure conditions, including solution pH, ionic strength and composition [ 22 , 50 ]. The synthetized GO shows a high dispersion stability in ultrapure water up to 72 h, monitored by UV–VIS and DLS measurements ( Figure S2, supplementary information ).…”
Section: Resultsmentioning
confidence: 99%
“…Data interoperability is especially important in a regulatory context, where standardised guidelines (e.g., OECD, ISO) need to be followed during experimental practice and becomes even more prominent as computational tools and workflows come into the picture. As a result, protocol and medium harmonisation are of the utmost importance as several cytotoxicity meta-analysis studies have stressed and demonstrated a significant correlation between the type of assay and medium used and the resulting hazardous effects [ 20 , 21 , 22 ]. To achieve this, the Horizon 2020 e-infrastructure project NanoCommons ( ) has been developing a cloud-based Knowledge Base, which links nano-related databases, and provides data curation and storage solutions linking information about the nanomaterials, their medium or environmental conditions and the overall test conditions to the resulting effect data, enabling tracking of changes to the particles over the experimental timeframe.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is also important to adequately characterize the exposure‐water chemistry in nano‐Ni toxicity tests, because dissolved Ni released from nano‐Ni can sometimes reach or exceed toxic concentrations in some water chemistries (Geitner et al 2020; and see Source of nano‐Ni toxicity: Nano‐Ni particles or dissolved Ni? ).…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the key drivers of toxicity in these assessments are not clear in some cases, and the observed effects may be caused by their bulk counterparts and released ions or degradants instead of the nanomaterials themselves. Therefore, the selection of appropriate methods to identify nanomaterials and differentiate their toxicity from bulk counterparts is imperative (Geitner et al 2020). Such a finding is partially attributable to the fact that there has been increasing evidence to show that many nanomaterials are not consistently more toxic to living organisms when compared with their bulk counterparts (Wiesner 2019).…”
Section: What Are the Terrestrial And Aquatic Risks Of Atmospheric Comentioning
confidence: 99%